1998
DOI: 10.14214/sf.696
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of 14C-labelled reserve carbon in Pinus sylvestris seedlings during shoot elongation

Abstract: Lippu, J. 1998. Redistribution of 14 C-labelled reserve carbon in Pinus sylvestris seedlings during shoot elongation. Silva Fennica 32(1): 3-10.This study examined the later use of 14 C reserves formed in previous autumn in Scots pine (Pinus sylvestris L.) seedlings. The seedlings were allowed to photosynthesise 14 CO 2 in early September when shoot and needle growth was over. The following spring the seedlings were harvested in five samplings during the shoot growth period. The distribution and concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
(18 reference statements)
1
19
0
1
Order By: Relevance
“…Apparently our seedlings were not able to compensate for the lost foliage with stored carbohydrates, since even defoliation conducted once during the current growing season resulted in reduced growth. This is in accordance with Lippu (1998), who showed that carbon stored in the previous season had only a minor role in the growth of Scots pine seedlings in the following growing season. Similar to host response, defoliation during three or two consecutive years increased the colonization of low-biomass and presumedly less carbon-demanding ECM morphotypes, while two years of repeated defoliation decreased colonization of high-biomass morphotypes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Apparently our seedlings were not able to compensate for the lost foliage with stored carbohydrates, since even defoliation conducted once during the current growing season resulted in reduced growth. This is in accordance with Lippu (1998), who showed that carbon stored in the previous season had only a minor role in the growth of Scots pine seedlings in the following growing season. Similar to host response, defoliation during three or two consecutive years increased the colonization of low-biomass and presumedly less carbon-demanding ECM morphotypes, while two years of repeated defoliation decreased colonization of high-biomass morphotypes.…”
Section: Discussionsupporting
confidence: 92%
“…Timing of foliar damage within the growing season may thus have a diVerent eVect on biomass accumulation in diVerent parts of the tree depending on its growth phase. Early in the growing season, elongating shoots form the largest sink that is mainly fed by photosynthetically active needles from previous years, while stored carbohydrates play a less important role (Hansen and Beck 1994;Lippu 1998). After shoot elongation a high proportion of the resources are allocated to developing needles, which gradually shift from carbon sinks to photosynthesizing sources towards the end of the season (Ericsson 1978;Troeng and Linder 1982).…”
Section: Introductionmentioning
confidence: 99%
“…3 B). Although shoot elongation is considered to depend on current assimilation (Ericsson 1978;Hansen and Beck 1994;Lippu 1998;von Felten et al 2007), our results suggested that alternative response mechanisms might be possible. Generally, HI was affected by weather conditions in the year preceding growth, but later in the season (after July), after the cessation of height growth of Scots pine (Jansons et al 2011), thus suggesting that nutrient reserves have apparently had a certain effect on shoot elongation.…”
Section: Discussionmentioning
confidence: 75%
“…The maximum tree height is determined by hydraulic properties of wood (Ryan and Yoder 1997) and as a tree reaches this limit, height growth gradually decreases resulting in an explicit age trend of HI (Volosyanchuk 2002;Salminen and Jalkanen 2005). Height growth of Scots pine occurs during the first part of the vegetation period and this process is considered to depend mainly on current assimilation rather than on nutrient reserves (Ericsson 1978;Hansen and Beck 1994;Lippu 1998;von Felten et al 2007). Lanner (1976) proposed that HI of Scots pine is determined by two components: environmental (climatic) conditions during shoot elongation and the number of growth initials formed in the previous vegetation season.…”
Section: Introductionmentioning
confidence: 99%
“…Hansen and Beck (1994) reported that bud break and sprouting in spring is supplied by the recent photosynthates of the 1-year-old needles, while later in the summer, growth of the new shoots is supported by their own photosynthesis. Based on studies on one to two-year-old seedlings, Lippu (1998) concluded that height growth of Scots pine is to large extent (96%) based on photosynthates produced during the current year. Von Felten et al (2007) studied 30-year-old mountain pines on the alpine tree line and found that 42% of carbon used for new wood growth came from storage, but that the needles were built up almost completely from current-year photosynthates.…”
Section: Height Growth Of Scots Pinementioning
confidence: 99%